Effect of surface properties on the antithrombogenicity of silk fibroin/S-carboxymethyl kerateine blend films - Lee, KY; Kong, SJ; Park, WH; Ha, WS; Kwon, IC (VSP BV, 1998)
Polymeric blends of silk fibroin (SF) and S-carboxymethyl kerateine (SCMK) were prepared by the solvent casting method to study the effect of surface properties on the antithrombogenicity. The films of SF/SCMK showed better antithrombogenic properties than SF or SCMK alone. Among them, the film containing 50 wt% SCMK showed the best antithrombogenicity. When the SF/SCMK films were treated with methanol, the antithrombogenicity of the films was scarcely affected except the SF-rich ones. The enhanced antithrombogenic properties were explained in terms of polarity of the surface. The blend films showed an enhancement of polar contribution to surface free energy (gamma(s)(p)) and polar stabilization energy (I-SW). SF-rich films showed high gamma(s)(p) and I-SW values when treated with methanol. This change of surface properties was considered to be due to the fact that the conformational transition from random coil structure to B-structure of proteins may have affected the surface properties, especially the polar properties.
Keywords: ENZYME-IMMOBILIZATION; ADSORPTION; COMPATIBILITY; BLOOD